2010
DOI: 10.5343/bms.2010.1001
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Mangrove-Derived Organic Matter in Mangrove Associated Sponges

Abstract: Degradation of mangrove-derived organic matter in mangrove associated spongesHunting, E.R.; de Goeij, J.M.; Asselman, M.; van Soest, R.W.M.; van der Geest, H.G. General rightsIt is not permitted to download or to forward/distribute the text or part of it without the consent of the author(s) and/or copyright holder(s), other than for strictly personal, individual use, unless the work is under an open content license (like Creative Commons). Disclaimer/Complaints regulationsIf you believe that digital publicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…Bacterial endosymbionts of the sponge specimens were extracted from subsamples of sponge tissue (0.1 cm 3 ) in a Precellys 24 lysis/homogenizer (Bertin Technologies) using ∅ = 0.1-and 0.5-mm beads. Subsequent centrifugation was performed for 30 s at 11 000 × g (Hunting et al 2010a). We assessed bacterial metabolic diversity by community level physiological profiling using Biolog GN microplates containing 95 unique single substrates (Garland & Mills 1991, Garland 1997.…”
Section: Metabolic Diversity Of Sponge Bacterial Symbiontsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial endosymbionts of the sponge specimens were extracted from subsamples of sponge tissue (0.1 cm 3 ) in a Precellys 24 lysis/homogenizer (Bertin Technologies) using ∅ = 0.1-and 0.5-mm beads. Subsequent centrifugation was performed for 30 s at 11 000 × g (Hunting et al 2010a). We assessed bacterial metabolic diversity by community level physiological profiling using Biolog GN microplates containing 95 unique single substrates (Garland & Mills 1991, Garland 1997.…”
Section: Metabolic Diversity Of Sponge Bacterial Symbiontsmentioning
confidence: 99%
“…However, mangrove-derived dissolved organic matter (DOM) consists mainly of tannins and polyphenolic compounds (Maie & Jaffe 2006), which are structurally complex and recalcitrant to biodegradation (Field & Lettinga 1992, Koch et al 2005, Kristensen et al 2008. Increasing evidence suggests that only a limited number of bacterial and fungal species are able to degrade complex polyphenols and tannins (Bhat et al 1998) and it has indeed been demonstrated that sponges commonly associated with mangrove roots contain bacteria that are capable of degrading mangrove-derived DOM, while bacterial communities associated with sponges that are typical to reef environments appear less proficient in degrading mangrove-derived DOM (Hunting et al 2010a). It is therefore hypothesized that the presence of bacterial endosymbionts that are capable of degrading mangrove-derived DOM may explain the observed differences in species composition between mangrove and reef sponge communities.…”
Section: Introductionmentioning
confidence: 99%
“…Bacterial activity was analyzed by dehydrogenase enzyme activity via the reduction of 2-(p-iodophenyl)-3-(p-nitrophenyl)-5-phenyl tetrazolium chloride (INT) to formazan (INTF), since INT reduction proved an accurate assay of electron transfer system activities (ETSA) under both anaerobic and aerobic conditions (Smith and Mcfeters 1997;Hunting et al 2010). Bacterial cells were simultaneously sampled alongside the platinum electrodes (400 lL porewater sample).…”
Section: Analytical Techniquesmentioning
confidence: 99%
“…It should be noted, however, this approach is used to address the predictive potential of Eh and accurate estimations of denitrifications rates were beyond the scope of this study, provided that the approach is very likely to overestimate the actual process (Seitzinger, 1988). Overall respiratory capacity of th e bacter ial commun ity was approximated by dehydrogenase enzyme activity via th e reduction of 2-(p-iodoph en yl)-3-(p- Porewater probe Bacteria probe impermeable HDPE accurate assay of Electron transfer system activities (ETSA) under both anaerobic and aerobic conditions (Smith and Mcfeters, 1997;Bhupathiraju et al, 1999;Rozzi and Remigi, 2004;Hunting et al, 2010). Bacterial cells were simultaneously sampled alongside the platinum electrodes (400 µL porewater sample).…”
Section: Analytical Techniquesmentioning
confidence: 99%